VARIASI DIALEKTAL BAHASA TOMUAN (DIALECTAL VARIATION OF TOMUAN LANGUAGE) - Andi Indah Yulianti (Balai Bahasa Nusa Tenggara Barat, 2016)
Tomuan language is spoken by the people residing in East Kotawaringin and Lamandau district, Central Kalimantan. The problem to be answered in this research is to identify any variations of the language that appears on Tomuan language in Menthobi Raya and Bulik sub-district of Lamandau, Central Kalimantan. In general, this study aimed to identify the forms of dialectal variation that appears in the Tomuan language on those two districts. The theoretical benefits of this research expected is to provide an overview of how a variation of the language can be a differentiator for certain groups target. In addition, the practical benefits of this study, may be used as a strategic step in setting government policy politics of language and language preservation areas in Indonesia. Analysis of the data in this study is using two analytical methods, dialectometric method and lexicostatistics method sourced from the base of 200 Swades vocabulary and Culture Association Vocabulary (A, C, P, and R). The source data in this study is from local languages utterances made by people in the village of Lubuk Hiju, District Menthobi Raya, and the village of Guci in District of Bulik, Lamandau district, Central Kalimantan.